One-Pot Synthesis and Antimicrobial Activity of Novel α-Aminophosphonates Using TMG - B. Siva Kumar; Y. Haranadha Reddy; C. Radha Rani; G. Chnadra Sekhar Reddy (E-Journal of Chemistry)
α-Aminophosphonates (4a-j) were synthesized in one-pot simultaneous reaction of 4-bromo-3-methyl benzenamine (1), dimethylphosphite (3) and different aromatic aldehydes (2a-j) by Kabachnik-Fields reaction in the presence of tetramethylguanidine (TMG) (10 mole%) as catalyst in toluene at reflux temperature afforded 4a-j in good yields. All these compounds were found to exhibit moderate to good antimicrobial activity.